The effect of loss of foot sole sensitivity on H-reflex of triceps surae muscles and functional gait - Zhang, Fangtong; Sun, Mengzi; Qu, Feng; Lewis, Kelsey; Choi, Jung Hun; Song, Qipeng; Li, Li (Frontiers in Physiology, 2023)
Objective: To investigate the effects of foot sole insensitivity on the outcomes of the triceps surae muscle H-reflex and functional gait. Material and Methods: H-reflex of the triceps surae muscles during quiet standing and their relationship with functional gait, six-minute walking distance (6MWD) and timed-up-and-go duration (TUG) were compared between people who have more (n=13, 73.3±4.3 years old), or less (n=10, 73.5±5.3), sensitive tactile sensation. Their monofilament testing scores were 9.0±1.5 (range: 7-10) and 2.3±2.4 (range: 0-6) out of 10, respectively. Results: No differences were detected for H-reflex parameters between the groups. The less sensitive group showed reduced (p<.05) functional gait capacity compared to the other group, 380.4±52.7 vs. 463.5±47.6m for 6MWD, and 9.0±1.5 vs. 7.2±1.1s for TUG, respectively. A significant relationship (p<.05), worse functional gait related to greater H/M ratio, observed in the less sensitive group, was not exhibited in the other group. Conclusions: The modulation of the H-reflex of triceps surae muscles was more sensitive in people with peripheral sensory degeneration.